Therapeutic work in the midst of grief:: A literature review - De Santis, Matilda; Finlay, Linda (European Journal for Qualitative Research in Psychotherapy, 2018)
This article offers a brief review of the theory and existing literature in the psychotherapy field which explores the nature of therapeutic work while in the midst of grief. The paucity of research in the field is highlighted while more recent existential phenomenological studies offer a promising development. Critically examining current knowledge in this area, we aim to inform practice and suggest further avenues for research.